Modelo Ecuatoriano de Equilibrio General Aplicado - Pérez O, Wilson (2020)
Applied general equilibrium models are part of the traditional tools of analysis used to evaluate economic policies and to estimate the effects of exogenous shocks in an economy. The objective of this document is to present an Applied General Equilibrium Model for Ecuador. It is a static model that includes households, government, external sector and industries, based on the Social Accounting Matrix of 2001. This model constitutes a line of research that aims to strongly contribute with the debate regarding the effects of the application of different economic policies in Ecuador.